Determination of mercury in river water by diffusive gradients in thin films using P81 membrane as binding layer - Colaco, Camila Destro [UNESP]; Marques Yabuki, Lauren Nozomi [UNESP]; Rolisola, Ana Marta [UNESP]; Menegario, Arnaud Antonio [UNESP]; Almeida, Eduardo de; Suarez, Carlos Alfredo [UNESP]; Gao, Yue; Corns, Warren T.; Nascimento Filho, Virgilio Franco do (Elsevier B.V., 2014)
In this work, a device based on diffusive gradients in thin films (DGT) was evaluated for the determination of Hg(II) in river water. The DGT device was assembled with a cellulose phosphate ion exchange membrane (P81 Whatman) as a binding phase and agarose gel 1.5% (m/v) as a diffusive layer. Laboratory deployments showed that the binding of Hg2+ ([Hg-DGT]/[Hg-solution]) by P81 membrane was more effective (97%) than the Chelex 100 resin (80%).The effect of ionic strength, pH and potential interfering ions on Hg binding with DGT's was investigated. The results showed no significant effect on the binding of Hg(II) at pH range from 3.5 to 8.5 and at an ionic strength range from 0.0005 to 0.1 mol L-1. Uptakes of 50 mu g L-1 Hg(II) by P81 membrane were not affected by Fe, Mn, Zn, Cu, Ca and Mg at the concentration range of 200-1800 mu g L-1. Finally, the DGT device using the P81 as the binding layer was applied for in situ measurements of Hg in river water. For in situ measurements, the labile Hg concentration (from <2 to 13 ng L-1) was lower than 10% of the dissolved fraction (from 155 to 446 ng L-1). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Mercury; Labile; Diffusive gradients in thin films technique (DGT); P81 membrane; Cold vapor atomic florescence spectrometry